New application about cartel fighting in Turkey: Evaluation of the regret regulation - Okyar, Mete Cüneyt; Darıcı, Bülent; Öcal, Fatih Mehmet (SILA SCIENCE, 2011)
In this study; in Turkey, the economic and social problems that cause the cartel deal with the subject, mainly the 4054 dated "Protection of Competition Law"s application for issued, "The Regret Regulation" known as the "Cartel of Reveal to Order Active Cooperation to Regulation" on the basis discussed. These regulations in Turkey, competitive environment better responsible Competition Council by law the duties and authorities commented on the aims as well, the cartel to uncover and investigate the purpose of the Competition Authority with the active collaborations of a wealth of information provides. In this study; in Turkey oligopolistic markets competitive environment improvement to prevent the difficulties are discussed, these difficulties heavily are experiencing manufacturing industry competitive nature of the measure used for concentration indices, how analysis is to analyze. Research on competition in Turkey is focused on consumer apathy is dominant, so that the oligopolistic structure of Turkey's full compliance with competition rules is to determine the potential for improvement. In this context, about the last two years the Competition Authority made by the audits, in Turkey in the market perfectly competitive conditions approached regarding the mentality of the structure and Turkey's national competitiveness radically change the terms is not enough to say.
Keywords: Cartel; Competition protection; Regret regulation; National competitiveness; Concentration indices